Posterior continuous curvilinear capsulorhexis with anterior vitrectomy vs optic capture buttonholing without anterior vitrectomy in pediatric cataract surgery. Issue 7 (July 2022) - Kohnen, Thomas; Davidova, Petra; Lambert, Martin; Wenner, Yaroslava; Zubcov, Alina A.
Abstract : In pediatric cataract surgery, posterior buttonholing proved to be a safe and effective technique in a long-term follow-up of 6.5 years, leaving the growing vitreous intact. Abstract : Purpose: To investigate long-term complications after pediatric cataract surgery with implantation of a heparin-coated polymethyl methacrylate intraocular lens (PMMA IOL) and posterior continuous curvilinear capsulorhexis (PCCC) with anterior vitrectomy vs PCCC without anterior vitrectomy with optic capture buttonholing. Setting: Department of Ophthalmology, Goethe University, Frankfurt, Germany. Design: Prospective randomized clinical trial. Methods: Eyes with unilateral or bilateral congenital cataract without further pathologies or former surgeries were randomly assigned in 2 groups: cataract removal, IOL implantation, and PCCC with anterior vitrectomy (group A) or posterior optic buttonholing without anterior vitrectomy (group B). The main outcome measures were posterior capsule opacification (PCO), complication rates, and refractive development. Results: 58 eyes of 41 pediatric cataract surgery patients were included. The mean age at the time of operation was 66.05 months (±29.39). In group A (n = 26), 2 eyes required treatment for PCO, whereas the optic axis remained clear in all eyes in group B (n = 30), which was statistically insignificant. In addition, group B had a slightly lower rate of complications. The mean spherical equivalent after a mean postoperative follow-up of 6.5 years was −0.11 ± 2.51 diopters (D) (−5.0 to +4.0 D) in group A and −0.08 ± 2.14 D (−5.0 to +4.0 D) in group B, which was also statistically insignificant. Conclusions: Optic capture with a heparin-coated PMMA IOL proved to be a safe technique in the prevention of secondary cataract formation without a higher rate of complications and the necessity of vitrectomy.